Estabilidade de taludes de solos residuais de granito e de gnaisse - Moreira, José Eduardo (1974)
Part One is concerned with a methodology for the study of granitic-gnaissic residual slopes with an emphasis on its heterogeneities - with respect to stratigraphy, shear strength, permeability, infiltration - wich ultimately govern the potential sliding surfaces. The basic point is the understanding of the weathering profile and the geological history of the slope. The subsurface hidrology is discussed in regard to the geotechnical and geological investigations. Design methods based on the statistical decision theory are presented. In Part Two a case history of a landslide on talus material is presented. The "in situ" shear strength, compared to that obtained in laboratory, confirms the need of a thorough knowledge of the sliding mechanism. Owing to the special topographic configuration, high pore pressure developed, by artesianism, owing to the preferred infiltration along the rock-talus contact.